Desulfated Hirugen (Hirudin 54-65) Induces Endothelium-Dependent Relaxation of Porcine Pulmonary Arteries - Glusa, Erika (Thrombosis and Haemostasis, 1994)
Desulfated hirugen (hirudin 54-65) at concentrations from 0.1 to 2 μM was found to relax PGF2α-precontracted ring segments of porcine pulmonary arteries with intact endothelium. The relaxation was associated with a pronounced increase in cGMP in the vessels. This endothelium-dependent relaxant effect depended on the extracellular calcium ion concentration and was probably due to the release of endothelium-derived NO as indicated by its susceptibility to blockade of the NO synthesis by NG-nitro-L-arginine. In the presence of indomethacin (3 μM) the maximum hirugen effect was significantly diminished by about 25%. In contrast, neither the sulfated hirugen nor recombinant desulfato hirudin at equimolar concentrations exerted endothelium-dependent relaxation. Hence, the relaxant effect did not correspond to the anticoagulant activity. Desulfated hirugen can be assigned to the group of well-known peptides causing vasodilatation via an endothelium-dependent mechanism.